Proposal for Alzheimer’s diagnosis using molecular buffer and bus network - Preecha Yupapin; None Mitatha; Narongchai Moongfangklang; Nathaporn Suwanpayak; None Ma; None Ali; None Saktioto (My University, 2011)
Proposal for Alzheimer's diagnosis using molecular buffer and bus network S Mitatha1, N Moongfangklang1, MA Jalil2, N Suwanpayak3, T Saktioto4, J Ali4, PP Yupapin31Hybrid Computing Research Laboratory, King Mongkut's Institute of Technology Ladkrabang, Bangkok, Thailand; 2Ibnu Sina Institute of Fundamental Science Studies, Nanotechnology Research Alliance, Universiti Teknologi Malaysia, Johor Bahru, Malaysia; 3Nanoscale Science and Engineering Research Alliance (N'SERA), Advanced Research Center for Photonics, King Mongkut's Institute of Technology Ladkrabang, Bangkok, Thailand; 4Institute of Advanced Photonics Science, Nanotechnology Research Alliance, Universiti Teknologi Malaysia, Johor Bahru, MalaysiaAbstract: A novel design of an optical trapping tool for tangle protein (tau tangles, ß-amyloid plaques) and molecular motor storage and delivery using a PANDA ring resonator is proposed. The optical vortices can be generated and controlled to form the trapping tools in the same way as the optical tweezers. In theory, the trapping force is formed by the combination between the gradient field and scattering photons, and is reviewed. By using the intense optical vortices generated within the PANDA ring resonator, the required molecular volumes can be trapped and moved dynamically within the molecular buffer and bus network. The tangle protein and molecular motor can transport and connect to the required destinations, enabling availability for Alzheimer's diagnosis.Keywords: Alzheimer's disease, molecular diagnosis, optical trapping tool, molecular networks
Keywords: Photoreceptor and optogenetics research